2018
DOI: 10.3390/ijerph15122715
|View full text |Cite
|
Sign up to set email alerts
|

Selected Risk Factors of Developmental Delay in Polish Infants: A Case-Control Study

Abstract: Despite a number of studies on the risk factors of developmental delay (DD) in children conducted in developed countries, Polish data are scarce, which hinder an early diagnosis and initiation of prevention/control measures. Objective: To assess selected risk factors of DD in infants. A case-control survey was conducted in 2017–2018 on 50 infants (≤1 year old) with DD and 104 healthy controls from three outpatient clinics in Szczecin, Poland. Data were collected using an anonymous questionnaire distributed amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Marzena Drozd-Dabrowska [17] confirmed that breastfeeding was related to lower risk of developmental delay in surveyed children, with similar results published by others. Additionally, breastfeeding was reported as an independent effect in relation to the developmental status at the 12th month of life [18].…”
Section: Discussionsupporting
confidence: 82%
“…Marzena Drozd-Dabrowska [17] confirmed that breastfeeding was related to lower risk of developmental delay in surveyed children, with similar results published by others. Additionally, breastfeeding was reported as an independent effect in relation to the developmental status at the 12th month of life [18].…”
Section: Discussionsupporting
confidence: 82%
“…During infancy, motor performance is a reliable manifestation of the functionality and integration of the central nervous system (1)(2)(3)(4)(5). Hence, the monitoring of infant motor development allows for detecting delays and disturbances and enabling, if necessary, early therapeutic interventions to prevent further structural and functional disorders (6).…”
Section: Introductionmentioning
confidence: 99%
“…In this study it was found that infants with birth weight of less than 2500gm were three times more likely to develop developmental delay as compare to infants with normal birth weight. [14] In another recent study by Pirhadi et al from Iran, the authors studied the relation of birth weight to the occurrence of developmental delay in children aged 4 to 16 months. In the study it was found that LBW of the child was associated with developmental delay in domains of fine motor movements, problem solving and total scores as assessed by ASQ.…”
Section: Discussionmentioning
confidence: 99%